Current Research Informing the Conceptualization, Identification, and Treatment of Dyslexia Across Orthographies: An Introduction to the Special Series. (August 2021) - Hall, Colby; Vaughn, Sharon
This introduction to the special series summarizes evidence for the genetic and brain bases for dyslexia and cognitive–behavioral indicators (including ones that can be measured even before the onset of reading instruction) that attest to meaningful differences between children with dyslexia and their non-dyslexic peers. Authors review controversies that have surrounded approaches to dyslexia identification and treatment during the last few decades. Finally, they introduce the findings of the articles in the special series and discuss potential implications for dyslexia identification and treatment.